PENGARUH METODE QISAH TERHADAP PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA SD NEGERI 77 BUTON - Mohammad Syaiful Anwar; Basri; La Jusu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Qishah method on improving learning motivation in Islamic Religious Education (PAI) among students at SD Negeri 77 Buton. The research employed a quantitative approach with a quasi-experimental design. The research sample consisted of two groups: the experimental group, which was taught using the Qishah method, and the control group, which was taught using the conventional lecture method. Data were collected through a learning motivation questionnaire, classroom observations, and teacher interviews, and analyzed using normality tests, homogeneity tests, and t-tests with the help of SPSS software. The results of the study indicate that the Qishah method significantly enhances students' learning motivation compared to the conventional method. The average learning motivation score of the experimental group increased from 65.2 to 85.7, while the control group only increased from 64.8 to 72.3. Statistical analysis showed a significance value (Sig. = 0.000), which is less than 0.05, indicating a significant difference between the two groups after the intervention. In addition to increasing motivation, the Qishah method also contributes to students' character development through the moral values embedded in the stories.